ANALISIS IMPLEMENTASI PENGAWASAN CUKAI HASIL TEMBAKAU DI PROVINSI LAMPUNG (STUDI PADA KANTOR WILAYAH DIREKTORAT JENDERAL BEA CUKAI SUMATERA BAGIAN BARAT) - Agus Purnomo; Yossef Ariyansyah (Universitas Bandar Lampung (UBL), 2020)
The problems in this study are: (1) How is the Implementation of Tobacco Product Excise Control in Lampung Province, (2) What aspects support and hinder the implementation of Tobacco Product Excise Control in Lampung Province. (3) Efforts made in Supervising Tobacco Product Excise in Lampung ProvinceThe research method used is qualitative with descriptive analysis method, the use of this method is to describe the Implementation of Tobacco Product Excise Control in Lampung Province, to study qualitatively, how all data is obtained directly from informants in the field using interviews and document studies.The results showed that in the implementation of Excise Control of Tobacco Products in Lampung Province. Performed in two ways, namely direct supervision by carrying out direct viewing and checking of the places that carry out the sale of cigarettes, and indirect supervision by using the application of Information Systems for the Distribution of Distribution and Distribution of Illegal Excissible Goods, as well as conducting monitoring through public reports that know where illegal cigarettes are circulated.What aspects that support, namely (1) The existence of technical guidelines for the implementation of tasks and (2) the availability of oversight budget while the aspects that uphold are, (1) Application Performance Stability that is less than optimal, (2) information System for Illegal Taxable Goods Distribution and Distribution Monitoring application data security factors that still need to be improved , (3) Inaccurate intelligence information, (4) Inadequate facilities and infrastructure, (5) Limited number of Human Resources (HR), (6) New Emerging Actors, (7) Low price of cigarettes illegal.The efforts made in the Supervision of Tobacco Product Excise, namely (1) continued to be socialized so that the level of compliance of cigarette sales entities increased, (2) the development of cigarette Small and Medium Industry Growth, (3) Support from local governments, (4) Government policies on industry Small and Medium Enterprises, (5) Strive (6) Follow-up handling of cases of violations in the field of Excise carried out in a massive and comprehensive manner to provide a deterrent effect.